MoTup1 is required for growth, conidiogenesis and pathogenicity of Magnaporthe oryzae. (27th February 2015) - Chen, Yue; Zhai, Su; Sun, Yi; Li, Mengying; Dong, Yanhan; Wang, Xiaoli; Zhang, Haifeng; Zheng, Xiaobo; Wang, Ping; Zhang, Zhengguang
Summary The general transcriptional repressor Tup1 proteins play important regulatory roles in the growth and development of fungi. In this report, we characterized MoTup1, a protein homologous to Tup1 of Saccharomyces cerevisiae, from M. oryzae. Disruption of MoTUP1 resulted in severe mycelial growth reduction and a defect in conidiogenesis. We found that MoTup1 is required for the maintenance of cell wall integrity by regulating the expression of the genes involved in cell wall biosynthesis. Pathogenicity assays indicated that the ΔMotup1 mutants lost the ability to invade both rice and barley hosts. Moreover, observation of rice epidermis penetration showed that the hyphal tips of the mutants could still form appressorium‐like structures, but were unable to invade host cells. Taken together, our results demonstrate that M. oryzae MoTup1 is an important regulatory factor in fungal growth, development and pathogenesis on hosts.